PEMETAAN LINEAR NON SINGULAR YANG MENGAWETKAN MATRIKS KUADRAT NOL DI KEDUA SIS - , FARIDHA NOOR CHASANAH, S. Si ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Let F be a field. Nn(F) denotes the matrices algebra consisting of all nxn upper triangular matrices over F with all of the diagonal component is zero. AÃ Nn(F) is said to be square zero if A2=0. We discuss non singular linear maps on Nn(F) which preserve square zero matrices in both directions.